IMPROVING SKILLS SPEAKING INDONESIAN DIALOGUE THROUGH APPLICATION OF VERBAL RESPONSE MODEL WITH IMAGES (Quasi-Experimental Study on Class X SMA Al-Ma'arif Mataram Mataram City) - Mustamin Mustamin (CIVICUS : Pendidikan-Penelitian-Pengabdian Pendidikan Pancasila dan Kewarganegaraan, 2016)
Abstract: Based on the above, the problems revealed in this study were 1) how much improvement students' speaking skills after participating in learning to talk by using a model of verbal response, and 2) how to change the behavior of students after participating in learning conversational skills using verbal response models. The purpose of this study were 1) determine students 'speaking skills improved after participating in learning conversational skills using verbal response models, and 2) assess changes in students' behavior after participating in learning conversational skills using verbal response models. This research is a quasi experimental study. Thus, the method used is a quasi-experimental design with pretest and posttest with experimental classes that give preferential treatment to the subject of the study, which compared with the control class. The research data was taken through tests, observations, questionnaires (questionnaire). Test data retrieval tool that is used in the form of test instruments act which contain aspects of evaluation criteria such as skills assessment through dialogue speaks Indonesian complete with pictures. Furthermore, the data were analyzed using t-test as a result of the quantitative data. Based on data analysis, it was concluded that the process of learning by verbal response models through pictures can improve students' speaking skills. Of 7.8%, the average value obtained by students at 73.4%, while the results achieved by 81.2%. Behavior that indicated the student had changed after being given treatment. Students are more enthusiastic learning, work well together in groups, not nervous or nervous and more confident when speaking in front of class.Hasil penelitian ini menyebutkan bahwa 1). Faktor-faktor yang mempengaruhi masyarakat di Desa Bonder Kecamatan Praya Barat Kabupaten Lombok Tengah melakukan perceraian tidak melalui Pengadilan Agama, antara lain disebabkan faktor ekonomi, faktor sosial dan kebiasaan masyarakat setempat, dan 2) Dampak yang ditimbulkan terhadap masyarakat di Desa Bonder Kecamatan Praya Barat Kabupaten Lombok Tengah yang  melakukan perceraian tidak melalui Pengadilan Agama meliputi a) Keabsahan perceraian terhadap perempuan yang diceraikan diluar pengadilan adalah ikatan perkawinan antara suami-istri tersebut belum putus secara hukum, perceraian tersebut sah secara hukum agama saja, b) Suami dan isteri masih mempunyai hak dan kewajiban terhadap pasangan masing-masing, c) Kedudukan anak yang dilahirkan dalam perkawinan setelah terjadinya perceraian.Abstract:Based on the above, the problems revealed in this study were 1) how much improvement students' speaking skills after participating in learning to talk by using a model of verbal response, and 2) how to change the behavior of students after participating in learning conversational skills using verbal response models. The purpose of this study were 1) determine students 'speaking skills improved after participating in learning conversational skills using verbal response models, and 2) assess changes in students' behavior after participating in learning conversational skills using verbal response models.This research is a quasi experimental study. Thus, the method used is a quasi-experimental design with pretest and posttest with experimental classes that give preferential treatment to the subject of the study, which compared with the control class. The research data was taken through tests, observations, questionnaires (questionnaire). Test data retrieval tool that is used in the form of test instruments act which contain aspects of evaluation criteria such as skills assessment through dialogue speaks Indonesian complete with pictures. Furthermore, the data were analyzed using t-test as a result of the quantitative data.Based on data analysis, it was concluded that the process of learning by verbal response models through pictures can improve students' speaking skills. Of 7.8%, the average value obtained by students at 73.4%, while the results achieved by 81.2%. Behavior that indicated the student had changed after being given treatment. Students are more enthusiastic learning, work well together in groups, not nervous or nervous and more confident when speaking in front of class.Hasil penelitian ini menyebutkan bahwa 1). Faktor-faktor yang mempengaruhi masyarakat di Desa Bonder Kecamatan Praya Barat Kabupaten Lombok Tengah melakukan perceraian tidak melalui Pengadilan Agama, antara lain disebabkan faktor ekonomi, faktor sosial dan kebiasaan masyarakat setempat, dan 2) Dampak yang ditimbulkan terhadap masyarakat di Desa Bonder Kecamatan Praya Barat Kabupaten Lombok Tengah yang  melakukan perceraian tidak melalui Pengadilan Agama meliputi a) Keabsahan perceraian terhadap perempuan yang diceraikan diluar pengadilan adalah ikatan perkawinan antara suami-istri tersebut belum putus secara hukum, perceraian tersebut sah secara hukum agama saja, b) Suami dan isteri masih mempunyai hak dan kewajiban terhadap pasangan masing-masing, c) Kedudukan anak yang dilahirkan dalam perkawinan setelah terjadinya perceraian.